Diskursive Landeskunde: Spracharbeit - recht(s) extrem - Virtanen Alexandra (Czech Republic, 2025)
In a perception of our own or Foreign Cultures, we ascribe interpretations to specific situations that are shaped by our personal and selective experiences. Discourse-based cultural studies posit that these meanings are formed through conversation and discourse. Thus, cultural studies are intimately intertwined with language, arising and evolving through language usage and discourse. In this context, the following text presents a teaching example from a Finnish university German lesson to demonstrate how learners of German as a foreign language become active participants in the construction of meaning. They expand their opinions and question different positions in the discourse to comprehend and acknowledge them. Using the beginning of a coming-of-age novel as an authentic text on migration, learners engage in literary reception, enhancing oral and written communication skills while raising awareness of recognizing right-wing extremist language. Through discussions, learners explore social contexts and become conscious of symbols as linguistic tools.
Brünner Beiträge zur Germanistik und Nordistik